UV Sensor Embedded Wearable E-Textile Based on Reversible Photochromic Spiropyran and Flexible Joule Heater - Kim, Jihyun; Choi, Hae Woon; Kim, Bongseop; Kim, Eunkyung; Lee, Jiwon; Lee, Soyoung; Kim, Jonghyun (AMER CHEMICAL SOC, 2025)
This paper reports the development of electronic textiles (e-textiles) using integrated ultraviolet (UV) sensing. The device combined a screen-printed Joule heater with an electrosprayed spiropyran (SP) coating. SP undergoes reversible photoisomerization under UV irradiation, leading to a visible purple coloration and recovery upon heating. Digital image analysis revealed that red and green channel intensities decreased. In contrast, the blue channel remained stable, with ΔE*76 increasing proportionally to irradiation power and time. These optical metrics quantitatively confirmed the UV-dependent color transition of the SP. In addition, polydimethylsiloxane (PDMS) encapsulation improved durability; PDMS-coated textiles showed much smaller resistance variations than uncoated samples under bending, stretching, and fatigue tests. These results demonstrated that SP-based colorimetric sensing combined with flexible Joule heating is a practical and reusable approach for wearable UV monitoring.